PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN VARIABEL ASIMETRI INFORMASI, KETIDAKPASTIAN STRATEGIK DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Rumah Sakit Swasta di Provinsi Riau) - Oetary Triyani; Vince Ratnawati; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Purpose of this study was to examine the effect of budget participation on budgetary slack with information asymmetry, uncertainty of strategic and leadership style as moderating variable. The location study this object is a private hospital located in Riau Province. While the timing of this study in November 2015. The population in this study are a private hospitals located in Riau Province. Data used in this study are primary data. Data collection method used in this research is to use the instrument in the form of a questionnaire which was given the leadership of the hospital. The analytical method used in this study is multiple regression analysis. Based on the data collected and testing has been done on the problem by using regression analysis method, it can be concluded: 1) Participation budget significantly influence budgetary slack. 2) The interaction between budgetary participation and asymmetry of information has an effect on budgetary slack, so the information asymmetry is a moderating variable. 3) The interaction between budgetary participation and strategic uncertainty has an effect on budgetary slack, so strategic uncertainty is a moderating variable. 4) The interaction between budgetary participation and leadership style has no effect on budgetary slack, so the style of leadership is not a moderating variable.Keywords: Participation budget, budgetary slack, asymmetry information, uncertainty strategic and leadership style